Riego por gravedad microaspersión y fertilización en plantilla de cacao theobroma cacao en Pasaje - Puglla Puglla, Tarkino de Jesús (2012)
On the site of the Parish Huizho "Casacay" located at km 11 of the Cuenca canton belonging to Passage, El Oro Province, Region 7 was investigated on fertilization to mase ammonium nitrate, ammonium phosphate and potassium nitrate applied as fertilizer integrated background with two irrigation systems, micro spray and gravity . The objectives were: 1.Establish the best gravity irrigation system and micro spray cocoa template. 2. Determining the best dose of fertilization. 3. Conduct an economic analysis of the treatments. According to the natural life zones of Holdridge and ecological map of Ecuador, the test site corresponds to a pre dry forest - montane (bs - PM) with an average annual rainfall of 500-1000 mm, a mean annual temperature of 24 º C. The materials used in this research were: cocoa plants, CCN -51, Tanks 1000 L, Piola, Film, Irrigation System, GPS, tensiometers, fertilizers; NO3NH4, DAP (NH4) 2HPO and KNO. The trial was conducted in a cocoa plantation, template-eight plants were selected for treatment, so the pipe mannifull serve as the core of each plot, consisting of a control stopcock at the beginning of each irrigation module. The plant selection was random, we selected 160 plants per plot, with ages ranging from two months, who presented the best botanical characteristics, physiological study used for the cocoa plant (Theobroma Cacao) CCN-51 graft from of the same generation plant site. According to the model of the cocoa seed and as the distribution system of sprinklers in the field (2.5 x 2.5), the number of sprinklers per plot was calculated as APT = Ground area; AMT = theoretical wet area sprinkler (8.62 m2), m2 Thus in each plot was irrigated by three sprinklers. 2 was used irrigation systems resulting from the combination of the layers of water (irrigation times) by gravity and micro with 4 treatments and 5 replicates for each method of irrigation totaling 40 experimental units. The variables studiedwere determinedby counting the number of fallen flowersafter gravity irrigation and microsprinkler andassessed the percentage ofeach treatmentfallen flowers. Bearing floralnumber, number of ears infected, measurement of water depth, plant height androot massat the beginning andend of the trial. The number offallen flowerswas higher inthe plotirrigatedbymicrospraytechnique, a situation that may be transientin time,the number of earsinfectedbydiseases ofcrop wassignificantly higher in themicro irrigation system spray; Inthesprinklersystemhadbetter conditionspredisposingtothe development of diseasesespecially"Monilla" theshoot growthof plantsinthe plotswere similarwith the twoirrigation systems, because it is aphysiological process, typical of the variety andonly dependent onthe levels offertility andfertilizationbackground withammoniumnitrate, ammoniumPhosfatopotassium nitrateplantsshowed betteraverageinshoot growth, especially withthe average dose of fertilizer